Global burden and trends of high BMI-attributable chronic kidney disease: a comprehensive analysis from 1990 to 2021 and projections to 2035 - Huifang Tan; Zhifu Liu; Yongjie Zhang; Kehao Yang; Yiming Zeng; Guoli Li; Zheng Xiao; Yuanwei Li; Yinyin Chen (Frontiers in Nutrition)
BackgroundHigh body mass index (BMI) is a major modifiable risk factor for chronic kidney disease (CKD), significantly contributing to its global burden. This study aimed to systematically evaluate the global burden of CKD attributable to high BMI from 1990 to 2021, identify demographic and regional variations, evaluate contributing risk factors, and project future trends through 2035.MethodsThe population-based analysis utilized data from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2021, encompassing 204 countries and territories across 21 GBD regions. Age-standardized mortality rate (ASMR) and age-standardized disability-adjusted life years rate (ASDR) were assessed using percentage change (PC) and estimated annual percentage change (EAPC). Decomposition analysis quantified drivers of mortality and DALYs changes, while Bayesian age-period-cohort models projected future trends.FindingsFrom 1990 and 2021, the ASMR of CKD attributable to high BMI increased from 2.69 (95% UI: 1.37–4.14) to 5.06 (95% UI: 2.7–7.5) per 100,000, and the ASDR rose from 69.13 (95% UI: 35.06–106) to 122.08 (95% UI: 66.25–180.18) per 100,000. Projections estimate continued to increase by 2035, with ASMR reaching 5.81 (95% UI: 3.55–8.07) and ASDR 149.42 (95% UI: 99.45–199.39) per 100,000. Sex and age disparities were evident: males showed higher ASR increases and earlier onset of disease burden, while older females experienced a higher overall burden. Regionally, low- and low-middle SDI areas exhibited the most rapid burden escalation, while some high-income countries achieved burden reduction. Among the attributable etiologies, hypertension and type 2 diabetes mellitus (T2DM) were predominant, with hypertension more common in males (42.05%) and T2DM in females (43.71%).ConclusionThe global burden of CKD attributable to high BMI has risen markedly over the past three decades, with widening disparities by geography, age, and sex. The COVID-19 pandemic may have further complicated risk dynamics and data quality. These findings highlight an urgent need for globally coordinated, locally adapted prevention strategies, particularly targeting younger males and populations in low-SDI regions.